Are “new” donors challenging World Bank conditionality? - Hernández, Diego (World development, 2017)
This paper investigates whether World Bank conditionality is affected by the presence of “new” donors by using panel data for 54 African countries over the 1980-2013 period. Empirical results indicate that the World Bank delivers loans with significantly fewer conditions to recipient countries which are assisted by China. In fact these receive 15% fewer conditions for every percentage-point increase in Chinese aid. Less stringent conditionality is also observed in better off borrowers that are in addition funded by Kuwait and the United Arab Emirates, but this effect vanishes after the start of the new millennium. In contrast, World Bank conditionality is rarely affected by aid inflows from DAC donors, and when it is, conditionality is revised upward. These findings suggest that new donors might be perceived as an attractive financial option to which the World Bank reacts by offering credits less restrictively in order to remain competitive in the loan-giving market and thereby cope with excesses in the supply of development resources.
Gesehen am 11.08.2021